HDAC1 Promotes Myocardial Fibrosis in Diabetic Cardiomyopathy by Inhibiting BMP-7 Transcription Through Histone Deacetylation - Ouyang, Chun; Huang, Lei; Ye, Xiaoqiang; Ren, Mingming; Han, Zhen (Experimental and Clinical Endocrinology & Diabetes, 2022)
Objective Diabetic cardiomyopathy (DCM) constitutes a primary cause of mortality in diabetic patients. Histone deacetylase (HDAC) inhibition can alleviate diabetes-associated myocardial injury. This study investigated the mechanism of HDAC1 on myocardial fibrosis (MF) in DCM.Methods A murine model of DCM was established by a high-fat diet and streptozotocin injection. The bodyweight, blood glucose, serum insulin, and cardiac function of mice were analyzed. Lentivirus-packaged sh-HDAC1 was injected into DCM mice and high glucose (HG)-induced cardiac fibroblasts (CFs). The pathological structure of the myocardium and the level of myocardial fibrosis were observed by histological staining. HDAC1 expression in mouse myocardial tissues and CFs was determined. Collagen I, collagen III, alpha-smooth muscle actin (α-SMA), and vimentin levels in CFs were detected, and CF proliferation was tested. HDAC activity and histone acetylation levels in tissues and cells were measured. Bone morphogenetic protein-7 (BMP-7) expression in myocardial tissues and CFs was determined. Functional rescue experiments were conducted to confirm the effects of histone acetylation and BMP-7 on myocardial fibrosis.Results DCM mice showed decreased bodyweight, elevated blood glucose and serum insulin, and cardiac dysfunction. Elevated HDAC1 and reduced BMP-7 expressions were detected in DCM mice and HG-induced CFs. HDAC1 repressed BMP-7 transcription through deacetylation. HDAC1 silencing alleviated MF, reduced CF proliferation and decreased collagen I, -III, α-SMA, and vimentin levels. However, reducing histone acetylation level or BMP-7 downregulation reversed the effects of HDAC1 silencing on CF fibrosis.Conclusion HDAC1 repressed BMP-7 transcription by enhancing histone deacetylation, thereby promoting MF and aggravating DCM.
Keywords: HDAC1; diabetic cardiomyopathy; myocardial fibrosis; histone acetylation; BMP-7; cardiac fibroblasts